Oxford photo dictionary (Practice exercises for classroom use or self-study) (Oxford Univ. Press, 1999)
The book presents over 2.400 words (both British and American English), colours photographs. Topiocs cover the family, the human body and the clothes, the home and the city, shops and food, the post office, money and the bank, school and work, science and the environment, travel, sport and animals.